Review on Characteristics and Analytical Methods of Remogliflozin Etabonate: An Update - Suryavanshi, Vallabh D.; Sharma, Sanjay; Sahu, Jagdish K. (Mini Reviews in Medicinal Chemistry, 2022)
Hyperglycemia and its associated disorders like Diabetes mellitus are engulfing the world’s population at a faster pace. New-age medications like the SGLT 2 inhibitors have found their place in the run to combat DM. Drugs with these properties have proven to be effective in treating hyperglycemia, obesity, and major cardiac disorders. The interesting fact about these drugs is that they act independently of insulin levels in the patient’s body. The fact that they even bypass the side effects shown by currently used anti-diabetic medications has attracted the world’s hope to neutralize diabetes mellitus. The invention of Remogliflozin Etabonate (RGE), an SGLT 2 inhibitor, has therefore added a silver lining to the gliflozin-family of drugs in the fight against DM. This is due to its least side effects as well as its effective mechanisms to treat hyperglycemia. It can be administered not only as a single entity but also can be co-administered in combination with other anti-hyperglycemic agents. RGE is already sold in the Indian market as REMO-ZEN, by Glenmark Pharmaceuticals. It has been studied thoroughly for its pharmacokinetic and pharmacodynamic profile. It is a benzylpyrazole glucoside. Various analytical methods have been formulated for its detection, quantification, and routine quality control activities. RGE can be studied with the help of UV-visible spectrophotometry, High-Performance Liquid Chromatography (HPLC) and Hyphenated techniques like Liquid Chromatography- Mass Spectroscopy (LC-MS/MS). This review briefs about the overall chemical, pharmacological, pharmacokinetic and pharmacodynamics properties of RGE. It mainly discusses various analytical techniques used for determining and estimating RGE.
Keywords: SGLT2 inhibitors